Sårbarhetens mysterium - Stålsett, Sturla J. (Dansk Teologisk Tidsskrift, 2019)
Globalization strengthens mutual interdependency between persons, nations and peoples. Such dependency implies exposed and experienced vulnerability. The significance of religion in people's lives seems to increase with their experience of insecurity. Whereas secularization continues where people enjoy a basic level of welfare and security, the perceived importance and impact of religion is generally increasing around the globe, due to globalized experiences of precariousness and vulnerability affecting the majority. This situation raises the question of how different forms of religiosity relate to people’s sense of vulnerability. In this article I explore in what ways a Lutheran and ecumenical theological approach inspired by liberation and feminist theologies may provide resources that make it possible to see human vulnerability as a value and strength that should be protected, not removed. Might vulnerability even be perceived as sacred? Can God be seen as a deus vulnerabilis? I also ask in what ways liturgical practice may visualize and operationalize such a theology of vulnerability.